2017
DOI: 10.3382/ps/pex134
|View full text |Cite
|
Sign up to set email alerts
|

Serological investigation of Mycoplasma synoviae infection in China from 2010 to 2015

Abstract: Mycoplasma synoviae can cause worldwide respiratory diseases, synovitis, or subclinical symptoms in poultry. M. synoviae infection occurs throughout the yr and causes significant economic losses, including increased mortality, condemnations, medication, and live production cost. In the present study, the seroprevalence of M. synoviae among 44,395 non-vaccinated chickens from 21 provinces in China from 2010 to 2015 was estimated using ELISA. The overall seroprevalence was 41.19%. Seropositive rates in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…MS is a major bacterial pathogen affecting the poultry industry worldwide with infections incurring enormous economic losses (Kreizinger et al, 2017;Sun et al, 2017;Xue et al, 2017;Kursa et al, 2019). Clinical signs of MS infection include infectious synovitis, primarily of the hock joints and foot pads (Kleven et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…MS is a major bacterial pathogen affecting the poultry industry worldwide with infections incurring enormous economic losses (Kreizinger et al, 2017;Sun et al, 2017;Xue et al, 2017;Kursa et al, 2019). Clinical signs of MS infection include infectious synovitis, primarily of the hock joints and foot pads (Kleven et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence in China varied in diff erent provinces from 5.10% to 100%. Commercial vaccine is not yet available in China, so the authors concluded that detected antibodies originated from the natural infection (Xue et al, 2017). In Serbia, the situation in view of the availability of vaccine against Ms is the same as the one in China, so our results indicated seroconversion following natural infection as well.…”
Section: Discussionmentioning
confidence: 60%
“…Since Ms can be transmitted vertically and horizontally (Stipkovits and Kempf, 1996), it can cause infection in broilers with increased mortality, feed conversion and condemnation. (Xue et al, 2017;Moreira et al, 2015). Feberwee et al (2008) reported lower seroprevalence in meat rearing breeder stock (6%) than in meat-type grandparents stock (10%), due to reduced risk of vertical transmission by elimination of Ms-positive fl ocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in layers, M. synoviae can induce shell abnormalities, causing a decrease in egg quality and production, increasing the operating costs ( Catania et al., 2010 ; Landman, 2014 ). Avian mycoplasmosis may be transmitted either vertically by broiler breeders through eggs ( Xue et al., 2017 ) or horizontally, often by direct contact between ill and unaffected carriers ( Marois et al., 2000 ). Moreover, Mycoplasma can remain in the flock constantly as forms ( Nascimiento et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%